Sinergi Guru Dan Orang Tua Dalam Pengawasan Penggunaan Gadget Anak Usia Dini Berdasarkan Nilai Keislaman - Mahdi, Nur Imam (AUD Cendekia: Journal of Islamic Early Childhood Education, 2024)
This study aims to analyze the synergy between teachers and parents in supervising gadget use among early childhood children based on Islamic values in the Environment 12 area of Binjai City. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation involving teachers, parents, and school principals in early childhood education (PAUD) and kindergarten institutions within the area. The findings reveal that the synergy between teachers and parents is formed through three main dimensions: (1) informative synergy, which involves sharing information about children’s digital behavior; (2) educative synergy, in which both parties cooperate to guide children in using gadgets in a healthy and purposeful manner; and (3) value-based synergy, reflecting a mutual understanding that digital supervision must be grounded in Islamic principles such as amanah (trustworthiness), adab (good manners), muraqabah (self-awareness of God’s supervision), iffah (modesty), and qana’ah (contentment). The study concludes that Islamic values function not only as a moral filter but also as an effective educational strategy in shaping children’s Islamic digital behavior. The collaborative model of teacher–parent partnership grounded in Islamic values represents the novelty of this research and offers a practical framework for early childhood education in the digital era.